Variability of water supply affected shoot biomass and root depth distribution of four temperate grassland species in monocultures and mixtures. (21st July 2020) - Haughey, Eamon; McElwain, Jennifer C; Finn, John A
Abstract: Aims: Research on the effects of extreme rainfall events on ecosystem function has primarily focussed on drought or flooding events, which usually include changes to mean or total rainfall, annually or over a season. However, less is known about the effects of increased rainfall variability without change to mean or total amounts. We investigated the effects of increased variation of water supply on shoot and root biomass as well as the distribution of root biomass of four grassland plant species, grown in monoculture and mixture communities. Methods: Perennial ryegrass ( Lolium perenne L., shallow-rooting grass), chicory ( Cichorium intybus L., deep-rooting forb), white clover ( Trifolium repens L., shallow-rooting legume) and red clover ( Trifolium pratense L., deep-rooting legume) were established in mesocosms. Four plants of the same species were grown in monoculture communities and one of each species grown in four-species communities. Water supply was manipulated such that; compared with a baseline level with low variation in water supply, there was a treatment with medium variation (±40%) and another with high variation (±80%). Shoot and root biomass were measured, and vertical root distribution models fitted. Important Findings: Compared with the low variation treatment, shoot biomass was significantly reduced under high variation for white clover, red clover and four-species communities. Under all conditions, four-species communities produced more shoot and root biomass than predicted by species performance in monoculture (overyielding). Under increased water variation, chicory monocultures allocated a higher proportion of root biomass to deeper soil layers while the total root biomass of white clover monocultures was significantly reduced. These results indicate that increased variability of water supply can negatively affect the shoot and root biomass production of single and multi-species grasslands. There is a need for further investigation of water variation effects on the functioning of multi-species grassland systems at field scale.